The dimension of the moduli space of pointed algebraic curves of low genus. Issue 7 (3rd July 2023) - Stevens, Jan
Abstract: We explicitly compute the moduli space pointed algebraic curves with a given numerical semigroup as Weierstrass semigroup for many cases of genus at most seven and when possible describe the structure as cone over an explicitly given variety. We determine the dimension of the moduli space for all semigroups of genus seven.